Drug resistant TB: UK multicentre study (DRUMS): Treatment, management and outcomes in London and West Midlands 2008-2014 - Arnold,A; Cooke,GS; Kon,OM; Dedicoat,M; Lipman,M; Loyse,A; Butcher,PD; Ster,IC; Harrison,TS (Journal of Infection, 2016)
Objectives: Detailed information regarding treatment practices and outcomes ofMDR-TB treatment in the UK is required as a baseline for care improvements.Methods: 100 consecutive cases between 2008 and 2014 were reviewed retrospectively at 4MDR-TB treatment centres in England to obtain information on drug treatment choices, hospitaladmission duration and outcomes for MDR-TB.Results: Initial hospital admission was long, median 62.5 (IQR 20e106, n Z 92) days, and 13%(12/92) of patients lost their home during this period. Prolonged admission was associated withpulmonary cases, cavities on chest radiograph, a public health policy of waiting for sputum cultureconversion (CC) and loss of the patient’s home. Sputum CC occurred at a median of 33.5(IQR 16e55, n Z 46) days. Treatment success was high (74%, 74/100) and mortality low (1%, 1/100). A significant proportion of the cohort had “neutral” results due to deportation and transferoverseas (12%, (12/100)). 14% (14/100) had negative outcomes for which poor adherencewas the main reason (62%, 9/14).